Implementation of MDLC Method to Create Promotional Videos for Tahu Bakso Mak Cito - Putra, Kurnia Ramadhan; Fahrudin, Nur Fitrianti; Umaroh, Sofia (Journal of Social Sciences and Technology for Community Service (JSSTCS), 2024)
The use of technology has a good impact in various sectors, including the culinary industry. Tahu Bakso Mak Cito, located in Leuwiliang, Bogor, faces challenges in adapting to technology, especially for marketing. This community service aims to overcome the problems faced by Tahu Bakso Mak Cito in promoting its products. The proposed solution is to create promotional videos by utilizing multimedia for effective marketing. A SWOT analysis was first carried out to identify the challenges faced by Tahu Bakso Mak Cito, including limited marketing strategies, competition from larger food companies, low production scale, and short product shelf life. After the problem has been identified using the SWOT Analysis, video development is then carried out by following the multimedia development methodology, namely the Multimedia Development Life Cycle, which includes initialization, blueprint design, asset preparation, product development, as well as testing and validation. To overcome this problem, solutions are proposed, including multimedia and social media marketing strategies. It is hoped that the success of making a promotional video for Tahu Bakso Mak Cito can improve their marketing capabilities in this era of technological development, which is not only useful for increasing brand awareness, but also becomes an inspiration for entrepreneurship. The positive response from the owners of Tahu Bakso Mak Cito UMKM was that they felt it was helpful to promote this community service activity.